A Case report on the Diagnosis of a Rare Pleural Tumor With Endobronchial Ultrasound. Issue 10 (March 2015) - Gaspard, Dany; Raja, Haroon; Arya, Rohan; Abouzgheib, Wissam; Boujaoude, Ziad; Dalar., Levent
<x xml:space="preserve">Abstract</x> Abstract Convex endobronchial ultrasound (C-EBUS)–guided transbronchial needle aspiration (TBNA) is an effective tool for the diagnosis of hilar, mediastinal, and central parenchymal lung lesions. However, it has a limited utility for pleural-based masses. We report a unique case of a pleural synovial sarcoma recurrence that was diagnosed by C-EBUS. The patient had a history of inguinal synovial sarcoma. He presented with cough and chest pain. Imaging of chest revealed large right pleural mass. Bronchoscopy with EBUS-TBNA diagnosed pleural recurrence of synovial sarcoma. He underwent radical resection and pathological examination confirmed the diagnosis of pleural synovial sarcoma. He experienced complete recovery and resolution of symptoms. Synovial sarcoma should be included in the differential diagnosis of pleural masses. Convex EBUS-guided biopsies can provide adequate diagnosis of large pleural tumors adjacent to the central airways without need for more invasive diagnostic procedures.